The influence of heartwood on the pulping properties of Acacia melanoxylon wood - Lourenço, Ana (2013)
The pulping wood quality of Acacia melanoxylon was evaluated in relation to the presence of heartwood. The sapwood and heartwood from 20 trees from four sites in Portugal were evaluated separately at 5% stem height level in terms of chemical composition and kraft pulping aptitude. Heartwood had more extractives than sapwood ranging from 7.4% to 9.5% and from 4.0% to 4.2%, respectively, and with a heartwood-to-sapwood ratio for extractives ranging from 1.9 to 2.3. The major component of heartwood extractives was made up of ethanol-soluble compounds (70% of total extractives). Lignin content was similar in sapwood and heartwood (21.5% and 20.7%, respectively) as well as the sugar composition. Site did not infl uence the chemical composition. Pulping heartwood differed from sapwood in chemical and optical terms: lower values of pulp yield (53% vs 56% respectively), higher kappa number (11 vs. 7), and lower brightness (28% vs 49%). Acacia melanoxylon wood showed an overall good pulping aptitude, but the presence of heartwood should be taken into account because it decreases the raw-material quality for pulping. Heartwood content should therefore be considered as a quality variable when using A. melanoxylon wood in pulp industries